The Influence of Perceived Facility Provision and Work Motivation on Faculty Performance at Instituto Superior Cirstal Timor Leste - Antonio Guterres; Martinho Mendes Pereira (Eduvest - Journal of Universal Studies, 2025)
This study aims to determine the effect of learning facilities (X1) and work motivation (X2) on lecturer performance (Y) at the Faculty of Teacher Training and Education, Instituto Superior Cristal. This quantitative research compares the independent variables (X1, X2) with the dependent variable (Y) using a questionnaire as a measurement instrument. Regression analysis shows that learning facilities (X1) have a significant influence on lecturer performance with a coefficient of 0.195 and a significance value of 0.022 (<0.05). Work motivation (X2) also shows a significant influence on lecturer performance with a coefficient of 0.812 and a significance value of 0.000 (<0.05). The combined effect of learning facilities and work motivation on lecturer performance was analyzed using multiple regression. The results show that the R square value is 0.774, which means that 77.4% of the variation in lecturer performance can be explained by the learning facilities and work motivation variables, while the rest (22.6%) is influenced by other factors. This study underscores the importance of providing adequate learning facilities and increasing work motivation in supporting lecturer performance to achieve effective and efficient learning objectives.